2012
DOI: 10.3109/02699206.2012.728278
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of disfluency with age from function to content words in Brazilian Portuguese speakers who do and do not stutter

Abstract: The purpose of this study was to investigate the exchange of disfluencies from function words to content words with age in Brazilian Portuguese speakers who do and do not stutter. Ninety stuttering individuals and 90 controls, native speakers of Brazilian Portuguese, were divided into three age groups (children, adolescents and adults). The study method involved analyzing the occurrence of stuttering on content and function words based on spontaneous speech samples. Results indicated that children tend to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…It may be that CWS between 7 and 10 years of age (age range of the children included in this study) experience more difficulties with open- than with closed-class words. Evidence that with increasing age, stuttering events decrease in closed-class words and increase in open-class words in many languages supports this (Au-Yeung, Gomez, & Howell, 2003; Dworzynki, Howell, Au-Yeung, & Rommel, 2004; Howell, Au-Yeung, & Sackin, 1999; Juste, Sassi, & Andrade, 2012). This suggestion could also explain why CWS tend to score lower on standardized measures of receptive vocabulary, which usually use open-class words, than do their normally fluent peers (Anderson & Conture, 2000; Murray & Reed, 1977; Ntourou et al, 2011; Pellowski & Conture, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…It may be that CWS between 7 and 10 years of age (age range of the children included in this study) experience more difficulties with open- than with closed-class words. Evidence that with increasing age, stuttering events decrease in closed-class words and increase in open-class words in many languages supports this (Au-Yeung, Gomez, & Howell, 2003; Dworzynki, Howell, Au-Yeung, & Rommel, 2004; Howell, Au-Yeung, & Sackin, 1999; Juste, Sassi, & Andrade, 2012). This suggestion could also explain why CWS tend to score lower on standardized measures of receptive vocabulary, which usually use open-class words, than do their normally fluent peers (Anderson & Conture, 2000; Murray & Reed, 1977; Ntourou et al, 2011; Pellowski & Conture, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…The effect of decreasing the speech rate is not desirable for individuals who stutter, since the own disorder, due to the excessive amount of disfluencies, causes a reduction in speech rate (24)(25)(26) or articulatory slowing (27) . A study of children with developmental stuttering, speakers of Brazilian Portuguese, showed that readiness in motor speech programming is slowed in relation to the control group of fluent children (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Function words, on the other hand, are a small closed class with just a grammatical value. This category includes prepositions, conjunctions, pronouns, auxiliary verbs, inflections and interjections (Juste et al, 2012).…”
Section: Lexical Densitymentioning
confidence: 99%